Hemodynamic Modifications in Patients with Symptomatic Unilateral Stenosis of the Internal Carotid Artery: Evaluation with MR Imaging Perfusion Sequences - Bozzao, Alessandro (AJNR Am J Neuroradiol, 2002)
BACKGROUND AND PURPOSE: Risk of developing ischemia is higher in patients with reduced cerebrovascular reactivity than in those with preserved cerebrovascular reactivity. Therefore, we assessed cerebral hemodynamic modifications in patients with unilateral stenosis of the internal carotid artery by using perfusion-weighted MR imaging to determine if these modifications underlie or anticipate ischemic signs and symptoms. METHODS: Fifteen patients with unilateral 70–90% carotid artery stenosis were studied with digital subtraction angiography and perfusion-weighted MR imaging. Their findings were compared with those of 15 age- and sex-matched control subjects. Regional cerebral blood volume (rCBV) and mean transit time (MTT) values were calculated in the middle cerebral artery and border zone territories. RESULTS: No significant difference was noted in rCBV and MTT values between the hemispheres in the symptomatic patients. There was a significant difference in MTT values in the border zones between patients and control subjects. MR images in patients and control subjects did not reveal large territorial infarcts and did reveal similar white matter lesion burdens. CONCLUSION: There is adequate compensation of unilateral stenosis when the stenosis is less than 90%. The risk of stroke is higher in patients with stenoses exceeding 70%, mostly because of decreased collateral reserve when confronted with emboli.